The crosstalk between microbial sensors ELMO1 and NOD2 shape intestinal immune responses - Aditi Sharma; Sajan Chandrangadhan Achi; Stella-Rita Ibeawuchi; Mahitha Shree Anandachar; Hobie Gementera; Uddeep Chaudhury; Fatima Usmani; Kevin Vega; Ibrahim M Sayed; Soumita Das (Virulence)
Microbial sensors play an essential role in maintaining cellular homoeostasis. Our knowledge is limited on how microbial sensing helps in differential immune response and its link to inflammatory diseases. Recently we have confirmed that ELMO1 (Engulfment and Cell Motility Protein-1) present in cytosol is involved in pathogen sensing, engulfment, and intestinal inflammation. Here, we show that ELMO1 interacts with another sensor, NOD2 (Nucleotide-binding oligomerization domain-containing protein 2), that recognizes bacterial cell wall component muramyl dipeptide (MDP). The polymorphism of NOD2 is linked to Crohn’s disease (CD) pathogenesis. Interestingly, we found that overexpression of ELMO1 and mutant NOD2 (L1007fs) were not able to clear the CD-associated adherent invasive E. coli (AIEC-LF82). The functional implications of ELMO1-NOD2 interaction in epithelial cells were evaluated by using enteroid-derived monolayers (EDMs) from ELMO1 and NOD2 KO mice. Subsequently we also assessed the immune response in J774 macrophages depleted of either ELMO1 or NOD2 or both. The infection of murine EDMs with AIEC-LF82 showed higher bacterial load in ELMO1-KO, NOD2 KO EDMs, and ELMO1 KO EDMs treated with NOD2 inhibitors. The murine macrophage cells showed that the downregulation of ELMO1 and NOD2 is associated with impaired bacterial clearance that is linked to reduce pro-inflammatory cytokines and reactive oxygen species. Our results indicated that the crosstalk between microbial sensors in enteric infection and inflammatory diseases impacts the fate of the bacterial load and disease pathogenesis.